Ti (C, N)-based cermets sintered under high pressure. (January 2016) - Wang, Yonghua; Kou, Zili; Liu, Yinjuan; Liu, Fangming; Duan, Wenrui; Deng, Jirui; Ma, Yinggong; Ma, Dejiang; Tan, Lijie; Li, Chunxia; Zhang, Yajie; He, Duanwei
Abstract: In this study, high pressure and high temperature sintering (HPHT) is adopted in the cermet fabrication process, and the microstructure and mechanical properties of cermets with TiC0.5 N0.5 –15WC–10Mo2 C–5TaC–10Ni–10Co (wt%) sintered under 5 GPa and different temperatures (900–1600 °C) using 6 × 14 MN cubic press are investigated. Results show that the densities of samples can reach up to 7.00 g/cm 3 . Vickers hardness and fracture toughness of the products are over 1727 HV30 and 7.2 MPa m 1/2 respectively. In addition, the sintering results are compared with the data that obtained from commercial samples which produced via conventional sintering technique. The conclusion is that high density and high hardness cermets can be obtained through HPHT sintering. Highlights: The products obtained via HPHT sintering have high density (7.00 g/cm 3 ), high hardness (1727HV30) and high fracture toughness (7.2 MPam 1/2 ). The particles can be cracked under high pressure. In addition, the crystalline size has not been obviously increased during the sintering. The BSEM micrographs of cermets. They are not the classical black (white) core/grey rim structures but even distributed three colors in the BSEM images.